Pengaruh Kualitas Laba dan Readability terhadap Biaya Modal Perusahaan Sektor Pertambangan yang terdaftar di BEI - Junaidi, Wahyu; Honesty, Fiola Finomia; Honesty, Helga Nuri (Jurnal Nuansa Karya Akuntansi, 2023)
The aim of this research is to determine the effect of earnings quality and readability on the capital costs of mining sector companies listed on BEI for the 2019 - 2022 period. The sample used was 55 mining sector companies registered on BEI. The data used is secondary data in the form of each company's annual report obtained from the official website of the Indonesian stock exchange and the company's official website. The data analysis used is descriptive analysis, normality testing and hypothesis testing using SPSS 25 software. Based on the results of this research, earnings quality has a significant positive effect on capital costs and readability has no significant effect on capital costs of mining sector companies listed in BEI for the 2019 - 2022 period.